THOUGHT PRESENTATION IN KATHRINE MANSFIELD’S SHORT STORIES (Journal of the College of Education for Women, 2019)
To cite the short stories of Kathrine Mansfield, all contain characters who arerevealed through their own thoughts. In her stories, the world is always seen throughthe eyes of her characters in the form of points of view presented to the readersthrough the characters' minds. This way of revealing characters and figuring out theworld, through the presentation of the characters' thoughts, is linked to the 'stream ofconsciousness.' Kathrine Mansfield has been compared with Virginia Woolf inparticular in that both writers used the thoughts and the points of view of theircharacters as material for their work through the stream of consciousness.According to Leech and Short (1981), there are five linguistic techniquesavailable for the narrator to present his/ her characters' thoughts through. These arethe direct thought, the free direct thought, indirect thought, free indirect thought andnarrative report of thought act. The narrator is free to use any, some or all of thesetechniques to inform the reader of what is going in the characters' minds to make him/her aware of certain points of view.The present paper attempts to present full exposition of the five techniques ofthought presentation mentioned above. This exposition is presented in the first sectionof the paper. The paper mainly aims at making a stylistic analysis of thoughtpresentation by the five techniques in Mansfield's short stories. The analysis is doneby investigating and examining the corpus which consists of thirteen short storieschosen randomly. The results of the analysis are presented through certainconclusions supported by statistics and examples which are quoted extracts chosenfrom the stories analysed. Almost each extract is accompanied by brief explanation ofpart of the plot which the extract is concerned with. The brief explanation helps thereader to comprehend both the extract and the conclusion arrived at.The paper is of a linguistic value and a literary value. The linguistic value liesin the full exposition of the five techniques of thought presentation and theirapplication on the literary corpus. A linguist can follow the same steps and apply thefive techniques on other literary works, whether short stories or novels. The literaryvalue lies in the analysis of the presentation of thought in a literary work (Mansfield'sshort stories) since there is a close link between the presentation of thought and thestream of consciousness which is a common technique of writing in many narrativeworks.